Refractory castable for blast furnace tapping main channel and preparation method of refractory castable

By using modified graphite and composite of magnesium carbide, boron carbide and silicon powder as antioxidants, the problems of insufficient corrosion resistance, thermal shock stability and oxidation resistance of the castable for the main groove of the blast furnace are solved, and higher slag corrosion resistance, thermal shock stability and oxidation resistance are achieved, and the service life is extended.

CN119874341APending Publication Date: 2025-04-25CHANGXING MINGTIAN FURNACE CHARGE

Patent Information

Application Number
CN202510093362.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing castables for iron discharge main grooves for blast furnaces have insufficient corrosion resistance, thermal shock stability and oxidation resistance, low carbon material addition, large amount of water added, and narrow oxidation temperature range.

Method used

Modified graphite is used as a carbon material, and MgO/Al2O3-coated graphite particles are formed through interfacial chemical deposition reaction and inert atmosphere calcination, and the surface of the end carboxylic polyethylene glycol silane is modified to improve oxidation resistance and dispersion. At the same time, the compounding of magnesium carbide, boron carbide and silicon powder is used as antioxidants to ensure good antioxidant effect within the entire high temperature range.

Benefits of technology

It significantly improves the slag corrosion resistance, thermal shock stability and oxidation resistance of the castable material, increases the amount of carbon materials, reduces the amount of water added, extends the service life, and improves the high temperature resistance and thermal shock resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005252206150000021
    Figure BDA0005252206150000021
  • Figure BDA0005252206150000031
    Figure BDA0005252206150000031
  • Figure BDA0005252206150000071
    Figure BDA0005252206150000071
Patent Text Reader

Abstract

The invention relates to a refractory castable for a blast furnace tapping main channel. The refractory castable is prepared from the following raw materials in parts by mass: 35-45 parts of compact corundum, 25-35 parts of white corundum, 12-18 parts of silicon carbide, 4-7 parts of alpha-Al2O3 micro powder, 2-5 parts of rho-Al2O3 micro powder, 6-10 parts of modified graphite, 1-5 parts of an antioxidant, 0.1-0.3 part of organic fibers and 0.05-0.2 part of a water reducing agent, the modified graphite is obtained by carrying out interface chemical deposition reaction on graphite oxide to form Mg (OH) 2 / Al (OH) 3 coated graphite particles, then calcining in an inert atmosphere to form MgO / Al2O3 coated graphite particles, and then carrying out surface modification by carboxyl-terminated polyethylene glycol silane. The antioxidant is a compound of magnesium carbide, boron carbide and silicon powder. The refractory castable for the blast furnace tapping main channel has excellent slag corrosion resistance, high temperature resistance and thermal shock resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a refractory castable for a blast furnace tapping main channel and a preparation method thereof. Background Art

[0002] The blast furnace tapping ditch is the channel connecting the blast furnace and the iron ladle, that is, the channel through which high-temperature molten iron and iron slag flow. Its lining is castable, which is a refractory material. The blast furnace tapping ditch is divided into the main ditch, branch ditch and slag ditch; the main ditch is the common channel for the mixture of high-temperature molten iron and iron slag flowing out of the blast furnace. A slag skimmer is designed at the rear section of the main ditch. The molten iron in the main ditch enters the branch ditch from the bottom of the slag skimmer, and the iron slag in the main ditch enters the slag ditch from the top of the slag skimmer beam. The main ditch is the most important and has the worst operating environment. It not only has to withstand the scouring of high-temperature molten iron, but also the erosion of high-temperature iron slag and thermal shock damage caused by sudden temperature changes. Therefore, the lining material of the main ditch, that is, the castable, has the highest performance requirements.

[0003] In order to resist the erosion of high-temperature molten iron and slag, carbon materials need to be added to the castable. Carbon has the characteristics of not being easily wetted by molten iron and slag, small thermal expansion coefficient and high thermal conductivity. The introduction of carbon materials can improve the erosion resistance and thermal shock stability of the iron outlet ditch. However, the addition of carbon materials will also bring new problems, mainly including: (1) Carbon materials are easily oxidized and lost in high-temperature use environments, which in turn leads to reduced corrosion resistance, thermal shock resistance and high temperature resistance of the castable; (2) Due to the poor water wettability of carbon materials, they are easy to float in the castable and difficult to disperse evenly. Therefore, the amount of carbon materials added in the prior art is relatively low, generally not exceeding 4%; (3) In order to effectively play the role of carbon materials, antioxidants need to be added to the castable, but the antioxidants in the prior art generally have a narrow antioxidant temperature range, which results in the carbon materials not being able to play their effective role better; (4) After the carbon material is introduced into the castable, in order to achieve appropriate fluidity, more water needs to be added to improve the construction performance. Generally, the amount of water added is more than 5% of the total mass of the castable, but after adding more water, the time required for the castable to dry will be greatly increased.

[0004] Chinese patent CN117247272A discloses an anti-oxidation blast furnace iron channel castable and its preparation method, wherein the raw material composition mass percentage is: 10.5-12% of 15-8mm brown corundum, 14.5-16% of 8-5mm brown corundum, 10-12% of 5-3mm brown corundum, 10-11% of 3-1mm brown corundum, 9-10% of 3-1mm dense corundum, 4-5% of 1-0mm dense corundum, 11-13% of 1-0mm silicon carbide, 325 mesh carbon Silicon dioxide is 9-10%, aluminum oxide powder is 4-6%, silicon powder is 1.5-2.5%, high alumina cement is 1-1.5%, ρ-Al2O3 is 1-1.5%, andalusite is 0.5-1%, spherical asphalt is 2-2.5%, carbon black is 0.5-1%, boron carbide is 0.2-0.4%, molybdenum strontium powder is 0.05-0.1%, metal silicon powder is 1.5-2.5%, metal aluminum powder is 0.02-0.04%, organic fiber is 0.04-0.07%, and water reducer is 0.1-0.3%. In the invention, a compound of spherical asphalt and modified carbon black is used as the carbon material, and molybdenum strontium powder, metal silicon powder and metal aluminum powder are used as antioxidants; wherein, the modified carbon black is obtained by impregnating the surface of carbon black with trimethyl aluminum, so that trimethyl aluminum reacts with the hydroxyl or carbonyl group on the surface of carbon black to form a chemical bond. The blast furnace iron ditch castable produced by the invention improves its anti-oxidation performance, thereby improving the performance and service life of the castable, but the maximum amount of carbon material added in the castable can only reach 3.5%, so its corrosion resistance and thermal shock stability need to be further improved, and the anti-oxidation temperature range is narrow. Summary of the invention

[0005] In the prior art, conventional carbon materials cannot effectively play their role, the addition amount is too low, the required amount of water is too much, and the anti-oxidation temperature range in the castable is narrow, which makes the corrosion resistance and thermal shock stability of the castable for the blast furnace iron main ditch need to be further improved. The present invention provides a refractory castable for the blast furnace iron main ditch to solve the above problems, improve the corrosion resistance, thermal shock stability and oxidation resistance of the castable for the iron main ditch, and have excellent pressure resistance.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A refractory castable for a blast furnace tapping main channel, comprising the following raw materials in parts by weight:

[0008]

[0009] The modified graphite is obtained by subjecting graphite oxide to an interfacial chemical deposition reaction in a mixed aqueous solution of Mg salt and Al salt to form Mg(OH)2 / Al(OH)3 coated graphite particles, then calcining in an inert atmosphere to form MgO / Al2O3 coated graphite particles, and then surface modification with terminal carboxyl polyethylene glycol silane; the antioxidant is a compound of magnesium carbide, boron carbide and silicon powder.

[0010] Carbon materials can enhance the ability to resist slag erosion and have high thermal conductivity. They are indispensable raw materials for refractory castables for iron troughs. However, conventional carbon materials are easily oxidized, which is detrimental to the compactness and erosion resistance of the castables. Conventional carbon materials have poor wettability with water, resulting in uneven dispersion in the matrix, so that the amount added is low and the amount of water added is high. The present invention obtains modified graphite by interfacial chemical deposition reaction, calcination in an inert atmosphere to form MgO / Al2O3 coated graphite particles, and then surface modification with terminal carboxyl polyethylene glycol silane. The inner layer of graphite in the modified graphite is coated with MgO / Al2O3, so as a carbon material, the oxidation resistance is significantly improved, thereby improving the compactness and slag erosion resistance of the castable; at the same time, its dispersibility and wettability with water are also greatly improved, thereby increasing the amount of carbon material added in the castable and reducing the amount of water added during the pouring construction stage, further improving the slag erosion resistance of the castable. On the other hand, in the subsequent production process of castables, MgO and Al2O3 coated on the graphite surface may react in situ to form magnesium aluminum spinel, which can improve the high temperature strength and thermal shock resistance of the castable; at the same time, the in-situ generated magnesium aluminum spinel has a small particle size, which is more conducive to the improvement of the castable's resistance to slag erosion than the "pre-synthesized" magnesium aluminum spinel. In addition, the modified graphite surface carboxyl-terminated polyethylene glycol silane has steric hindrance and wetting effects on other particles (corundum, silicon carbide, Al2O3 powder, etc.), so that when a small amount of water reducer is added, the castable also has good fluidity during the pouring construction process.

[0011] Furthermore, the mass ratio of the graphite oxide, Mg salt and Al salt is 10:(1.5-2.5):(3.5-6.5); the mass ratio of the MgO / Al2O3 coated graphite particles to the terminal carboxyl polyethylene glycol silane is 10:(0.6-1).

[0012] Furthermore, the structural formula of the carboxyl-terminated polyethylene glycol silane is:

[0013]

[0014] Wherein R is -CH3 or -CH2CH3, and the number average molecular weight of the polyethanol chain segment is 400-800.

[0015] Furthermore, in the antioxidant, the mass ratio of magnesium carbide, boron carbide and silicon powder is 1:(1-2):(1-2). Antioxidants react with oxygen before carbon at high temperatures. The present invention uses a compound of magnesium carbide, boron carbide and silicon powder as an oxidant, wherein magnesium carbide has a better antioxidant effect at 600-800°C, boron carbide has a better antioxidant effect at 800-1000°C, and silicon powder has an excellent antioxidant effect above 1000°C. The antioxidant formed by the compound of the three has a good antioxidant effect in the entire high temperature range.

[0016] Furthermore, the modified graphite is prepared by a method comprising the following steps:

[0017] (P1) thermally oxidizing graphite to obtain graphite oxide;

[0018] (P2) dissolving a nonionic surfactant in a mixed aqueous solution of Mg salt and Al salt, and then dispersing graphite oxide therein to obtain a suspension; then dropping an alkali solution into the suspension, and performing an interfacial chemical deposition reaction under stirring, and after the reaction is completed, washing, filtering, and drying to obtain Mg(OH)2 / Al(OH)3 coated graphite particles;

[0019] (P3) calcining the Mg(OH)2 / Al(OH)3 coated graphite particles under an inert atmosphere to obtain MgO / Al2O3 coated graphite particles;

[0020] (P4) MgO / Al2O3 coated graphite particles and carboxyl-terminated polyethylene glycol silane are added to a non-polar organic solvent, and the modified graphite is obtained after stirring and reacting.

[0021] Preferably, in step (P1), the graphite is at least one of artificial graphite, natural graphite, and graphitized mesophase carbon microspheres, and its particle size D50 is 10-15 μm; the thermal oxidation conditions are: 250-350°C for 1-3 hours. The thermal oxidation process is simpler, more efficient, and more environmentally friendly than the chemical reagent oxidation process. After thermal oxidation, the graphite has more active groups and active sites, which is beneficial to the subsequent interfacial chemical deposition reaction.

[0022] Preferably, in step (P2), the nonionic surfactant is a polyoxyethylene fatty acid ester, such as at least one of Sell Ze 49 or Sell Ze 52, and its dosage is 1-3wt% of the mixed aqueous solution; the Mg salt is at least one of MgCl2, MgSO4, and Mg(NO3)2, and the Al salt is at least one of AlCl3, Al2(SO4)3, and Al(NO3)3; the concentration of the Mg salt in the mixed aqueous solution is 0.5-1.5wt%, and the concentration of the Al salt is 1.5-3.5wt%; the alkali solution is an aqueous solution of NaOH or KOH, and its concentration is 5-10wt%, and its dosage is 0.4-0.8 times the mass of the mixed aqueous solution. After the alkali solution is added dropwise to the suspension, an interfacial chemical deposition reaction is carried out on the surface of the graphite oxide to generate Mg(OH)2 and Al(OH)3. In the present invention, the amount of the alkali solution is excessive to ensure complete precipitation of the Mg salt and the Al salt.

[0023] Preferably, in step (P2), the stirring speed is 60 to 120 rpm; the conditions of the interfacial chemical deposition reaction are: the temperature is 40 to 60°C, the alkali solution is added within 30 to 60 minutes and the stirring is continued for 20 to 40 minutes after the addition is completed; the washing is performed with pure water, and the filtration is performed until the pH value of the filtrate is 6.8 to 7.2; the drying conditions are: the temperature is 80 to 100°C and the time is 8 to 12 hours.

[0024] Preferably, in step (P3), the inert atmosphere is nitrogen and / or argon, and the calcination conditions are: keeping warm at 400-500° C. for 1-3 hours.

[0025] Preferably, in step (P4), the ratio of the MgO / Al2O3 coated graphite particles to the non-polar organic solvent is 10g: (80-150)mL; the non-polar organic solvent is at least one of toluene and xylene; the stirring reaction conditions are: heating to 50-60°C at a rotation speed of 150-300rpm and reflux reaction for 3-6h.

[0026] Furthermore, the particle size of the compacted corundum is 3-8 mm; the particle size of the white corundum is 1-3 mm; the particle size of the silicon carbide is 0.5-1 mm; the particle size D50 of the α-Al2O3 micropowder is 3-10 μm; the particle size D50 of the ρ-Al2O3 micropowder is 3-10 μm; and the particle size of the antioxidant is 200-400 meshes. In the present invention, different particle sizes of the raw materials of each component form a close stacking in an optimal ratio, that is, the gaps between the stacking of millimeter-level particles (compacted corundum, white corundum, silicon carbide) are filled with micron-level particles (modified graphite, antioxidant), and the gaps between the stacking of micron-level particles are filled with ultrafine powders (α-Al2O3 micropowder, ρ-Al2O3 micropowder), so that the whole system is tightly wrapped to form a complete and dense matrix structure, thereby improving the structural strength of the castable.

[0027] Furthermore, in the dense corundum and white corundum, Al2O3≥99wt%, Fe2O3≤0.1wt%, SiO2≤0.1wt%; in the silicon carbide, SiC≥97wt%, SiO2≤0.4wt%, Fe2O3≤0.3wt%; in the α-Al2O3 micropowder, Al2O3≥99.0wt%; in the ρ-Al2O3 micropowder, Al2O3≥98.0wt%.

[0028] Furthermore, the organic fiber is at least one of nylon fiber, polyethylene fiber and polypropylene fiber, and has a diameter of 4 to 8 μm and a length of 8 to 15 mm.

[0029] Furthermore, the water reducing agent is a polycarboxylic acid water reducing agent, and its water reducing rate is 18-22%.

[0030] In a second aspect, the present invention also provides a method for preparing the above-mentioned refractory castable for the main ditch of blast furnace iron tapping, comprising the following steps:

[0031] (S1) adding α-Al2O3 micropowder, ρ-Al2O3 micropowder, modified graphite and antioxidant into a container and mixing and stirring to obtain a mixed fine material;

[0032] (S2) adding dense corundum, white corundum and silicon carbide into another container and mixing and stirring to obtain mixed granules;

[0033] (S3) adding the mixed fine material obtained in (S1) to the mixed granular material obtained in (S2), and then adding organic fiber and a water reducing agent for mixing and stirring, thereby obtaining a refractory castable for a blast furnace main ditch.

[0034] Furthermore, the stirring in step (S1) is stirring at a speed of 500-800 r / min for 30-90 min; the stirring in step (S2) is stirring at a speed of 200-400 r / min for 10-30 min; and the stirring in step (S3) is stirring at a speed of 200-400 r / min for 10-30 min.

[0035] In a third aspect, the present invention also provides a method for adding water to pour the above-mentioned refractory castable for the main channel of blast furnace iron production, wherein the amount of water added is 3-5wt% of the refractory castable.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1) The present invention uses modified graphite as the carbon material, that is, MgO / Al2O3 coated graphite particles modified with terminal carboxyl polyethylene glycol silane as the carbon material, which significantly improves the oxidation resistance of graphite, thereby improving the compactness and slag erosion resistance of the castable; at the same time, it also greatly improves its dispersibility and wettability with water, thereby increasing the amount of carbon material added to the castable. The amount of modified graphite added in the present invention is more than 7%, and the amount of carbon material added in the prior art is difficult to exceed 4%. The increase in the amount of carbon material added further improves the slag erosion resistance of the castable.

[0038] 2) In the subsequent production process of the main iron channel castable, under high temperature conditions, the MgO coated on the surface of the inner graphite in the modified graphite may react with Al2O3 in situ to form magnesia-alumina spinel, which can improve the high temperature strength and thermal shock resistance of the castable. At the same time, the in-situ generated magnesia-alumina spinel has a fine particle size, which is more conducive to improving the castable's resistance to slag erosion than the "pre-synthesized" magnesia-alumina spinel.

[0039] 3) The modified graphite as a carbon material reduces the amount of water added during the pouring construction stage. In the present invention, the amount of water added during the pouring construction stage is only 3-5wt% of the castable. At the same time, the carboxyl-terminated polyethylene glycol silane modified on the surface of the modified graphite has steric hindrance and wetting effects on other particles (corundum, silicon carbide, Al2O3 powder, etc.), so that the castable has good fluidity during the pouring construction process when a small amount of water reducing agent is added.

[0040] 4) The present invention adopts a compound of magnesium carbide, boron carbide and silicon powder as an antioxidant, giving full play to the advantages of each component at different temperature stages; magnesium carbide has a good antioxidant effect at 600-800°C, boron carbide has a good antioxidant effect at 800-1000°C, and silicon powder has an excellent antioxidant effect above 1000°C; the composite antioxidant formed by the compound of the three ensures that the castable has a good antioxidant effect in the entire high temperature range.

[0041] 5) The refractory castable for the main ditch of the blast furnace iron-out of the present invention mainly comprises alumina and silicon carbide. Dense corundum, white corundum, α-Al2O3 powder and ρ-Al2O3 powder are the main sources of alumina; among them, dense corundum and white corundum have low porosity and high hardness, which can improve the castable's resistance to iron slag penetration; α-Al2O3 powder and ρ-Al2O3 powder can improve the fluidity of the castable, thereby improving the construction performance, and ρ-Al2O3 powder has the ability of spontaneous hydration at room temperature, which can act as a binder. Silicon carbide has the characteristics of high hardness, high strength, low thermal expansion coefficient and high thermal conductivity, which can improve the sintering strength and slag resistance of the castable. In addition, based on the packing density theory, the raw material particle size and ratio are preferably selected so that the entire system of the prepared castable is tightly wrapped to form a complete and dense matrix structure.

[0042] 6) In summary, the refractory castable for the main ditch of blast furnace iron tapping of the present invention has excellent slag erosion resistance, high temperature strength and thermal shock resistance. Its flexural strength in the cold state after firing at 1400℃×3h is above 12.5Mpa, its compressive strength is above 64Mpa, its linear change rate is lower than +0.3%, and its flexural strength in the hot state at 1400℃×0.5h is above 4.4Mpa. DETAILED DESCRIPTION

[0043] The present invention will be further described below in conjunction with specific embodiments.

[0044] Unless otherwise specified in the following examples, the reagents and materials described can be obtained from commercial sources.

[0045] Unless otherwise specified, the “parts” in the embodiments of the present invention are parts by mass, and the “%” are percentages by mass.

[0046] The graphite was selected from Qingdao Yuchen Graphite Co., Ltd., and the particle size D50 was 11.6 μm.

[0047] The carboxyl-terminated polyethylene glycol silane is selected from Chongqing Yusi Pharmaceutical Technology Co., Ltd., and its structural formula is

[0048]

[0049] The number average molecular weight of the polyethylene glycol segment is 600.

[0050] The particle size of dense corundum is 3-5mm, the particle size of white corundum is 1-3mm, the particle size of silicon carbide is 0.5-1mm, the particle size D50 of α-Al2O3 micropowder is 5.6μm, the particle size D50 of ρ-Al2O3 micropowder is 6.1μm, the particle size of magnesium carbide is 325 mesh, the particle size of boron carbide is 325 mesh, and the particle size of silicon powder is 325 mesh.

[0051] The polyethylene fiber was selected from Shandong OUDE Chemical Fiber Products Co., Ltd., with a melting point of 105°C, a diameter of 5-6 μm, and a length of 10 mm.

[0052] The polycarboxylate water reducer is selected from Liaoning Kelong Fine Chemical Co., Ltd., model S-409, and its water reduction rate is about 20%.

[0053] Preparation of modified graphite

[0054] Preparation Example 1

[0055] (P1) placing 500 g of graphite in an oxidation furnace, introducing oxygen at a flow rate of 0.4 L / min, maintaining the temperature at 300° C. for 2 h, and cooling to room temperature to obtain graphite oxide;

[0056] (P2) 1.5 g of MgCl2 and 3.5 g of AlCl3 were dissolved in 200 g of pure water to form a mixed aqueous solution, 3 g of NaCl49 was dissolved in the mixed aqueous solution, and 10 g of graphite oxide was dispersed therein to obtain a suspension; the stirring speed was turned on at 80 rpm, 90 g of a 7 wt% NaOH aqueous solution was added dropwise to the suspension over 40 min to carry out an interfacial chemical deposition reaction, and stirring was continued for 20 min after the addition was completed; after the stirring was completed, the filtrate was washed with pure water until the pH value of the filtrate was 7.0, filtered, and dried at 80°C for 12 h to obtain Mg(OH)2 / Al(OH)3 coated graphite particles;

[0057] (P3) calcining the Mg(OH)2 / Al(OH)3 coated graphite particles at 450°C for 1.5 h under a nitrogen atmosphere to obtain MgO / Al2O3 coated graphite particles;

[0058] (P4) 10 g of MgO / Al2O3 coated graphite particles and 0.6 g of terminal carboxyl polyethylene glycol silane were added to 100 mL of xylene, heated to 55°C for reflux reaction for 4 h with stirring at 200 rpm; then cooled, filtered, washed with pure water until the filtrate was colorless, and dried in an oven at 70°C for 24 h to obtain modified graphite a.

[0059] Preparation Example 2

[0060] The rest is the same as Preparation Example 1, except that the amount of materials used in steps (P2) and (P4) is different, specifically:

[0061] (P1) Same as Example 1;

[0062] (P2) 2.0 g of MgCl2 and 5.0 g of AlCl3 were dissolved in 200 g of pure water to form a mixed aqueous solution, 3 g of NaOH-49 was dissolved in the mixed aqueous solution, and 10 g of graphite oxide was dispersed therein to obtain a suspension; the stirring speed was turned on at 80 rpm, 100 g of a 7 wt% NaOH aqueous solution was added dropwise to the suspension over 40 min to carry out an interfacial chemical deposition reaction, and stirring was continued for 30 min after the addition was completed; after stirring, the mixture was washed with pure water until the pH of the filtrate was 7.0, filtered, and dried at 80°C for 12 h to obtain Mg(OH)2 / Al(OH)3 coated graphite particles;

[0063] (P3) Same as Example 1;

[0064] (P4) 10 g of MgO / Al2O3 coated graphite particles and 0.8 g of terminal carboxyl polyethylene glycol silane were added to 100 mL of xylene, heated to 55°C for reflux reaction for 4 h with stirring at 200 rpm; then cooled, filtered, washed with pure water until the filtrate was colorless, and dried in an oven at 70°C for 24 h to obtain modified graphite a.

[0065] Preparation Example 3

[0066] The rest is the same as Preparation Example 1, except that the amount of materials used in steps (P2) and (P4) is different, specifically:

[0067] (P1) Same as Example 1;

[0068] (P2) 2.5 g of MgCl2 and 6.5 g of AlCl3 were dissolved in 200 g of pure water to form a mixed aqueous solution, 3 g of NaOH 49 was dissolved in the mixed aqueous solution, and 10 g of graphite oxide was dispersed therein to obtain a suspension; the stirring speed was turned on at 80 rpm, 130 g of a 7 wt% NaOH aqueous solution was added dropwise to the suspension over a period of 50 min to carry out an interfacial chemical deposition reaction, and stirring was continued for 30 min after the addition was completed; after stirring, the mixture was washed with pure water until the pH of the filtrate was 7.0, filtered, and dried at 80°C for 12 h to obtain Mg(OH)2 / Al(OH)3 coated graphite particles;

[0069] (P3) Same as Example 1;

[0070] (P4) 10 g of MgO / Al2O3 coated graphite particles and 1 g of terminal carboxyl polyethylene glycol silane were added to 100 mL of xylene, heated to 55°C for reflux reaction for 4 h with stirring at 200 rpm; then cooled, filtered, washed with pure water until the filtrate was colorless, and dried in an oven at 70°C for 24 h to obtain modified graphite a.

[0071] Comparative Preparation Example 1

[0072] The rest is the same as Preparation Example 1, except that 3-[3-carboxyallylamide]propyltriethoxysilane is used in step (P4) instead of terminal carboxyl polyethylene glycol silane to finally obtain modified graphite d.

[0073] Comparative Preparation Example 2

[0074] The rest is the same as Preparation Example 1, except that steps (P2) and (P3) are omitted, and graphite oxide is used in step (P4) instead of MgO / Al2O3-coated graphite particles to finally obtain modified graphite e.

[0075] Example 1

[0076] A blast furnace iron tapping main ditch castable, comprising the following raw materials in parts by weight:

[0077]

[0078]

[0079] The preparation method comprises the following steps:

[0080] (S1) adding α-Al2O3 powder, ρ-Al2O3 powder, modified graphite and antioxidant into a container, stirring at a speed of 600 r / min for 30 min to obtain a mixed fine material;

[0081] (S2) adding dense corundum, white corundum and silicon carbide into another container, stirring at a speed of 200 r / min for 20 min to obtain mixed pellets;

[0082] (S3) maintaining a stirring speed of 200 r / min, adding the mixed fine material obtained in (S1) to the mixed granular material obtained in (S2), and then adding polyethylene fiber and polycarboxylic acid water reducer and mixing and stirring at a speed of 200 r / min for 20 minutes to obtain a refractory castable for the main ditch of blast furnace iron tapping.

[0083] Example 2

[0084] The rest is the same as Example 1, except that in the raw material composition, the modified graphite particles b prepared in Preparation Example 2 are used to replace the modified graphite a prepared in Preparation Example 1.

[0085] Example 3

[0086] The rest is the same as Example 1, except that in the raw material composition, the modified graphite particles c prepared in Preparation Example 3 are used to replace the modified graphite a prepared in Preparation Example 1.

[0087] Example 4

[0088] The rest is the same as Example 1, except that in the raw material composition, the antioxidant is 3 parts, including 0.6 parts of magnesium carbide, 1.2 parts of boron carbide, and 1.2 parts of silicon powder (i.e. 1:2:2).

[0089] Example 5

[0090] The rest is the same as Example 1, except that the raw material composition is:

[0091]

[0092]

[0093] Example 6

[0094] The rest is the same as Example 1, except that the raw material composition is:

[0095]

[0096] Comparative Example 1

[0097] The rest is the same as Example 1, except that in the raw material composition, the modified graphite d prepared in Comparative Preparation Example 1 is used to replace the modified graphite a prepared in Preparation Example 1.

[0098] Comparative Example 2

[0099] The rest is the same as Example 1, except that in the raw material composition, the modified graphite e prepared in Comparative Preparation Example 2 is used to replace the modified graphite a prepared in Preparation Example 1.

[0100] Comparative Example 3

[0101] The rest is the same as Example 1, except that the antioxidant does not contain magnesium carbide and silicon powder, that is, the antioxidant is 3 parts of boron carbide.

[0102] Testing and analysis

[0103] 4% of water was added to the refractory castables for the main trough of the blast furnace obtained in the above embodiment and comparative example, and stirred at 200r / min for 10min, and then vibrated on a vibration table to obtain a strip of 40mm×40mm×160mm in size. After 24h of mold curing in a normal temperature zone, the strip was demoulded, placed in a 110℃ oven for drying for 24h, kept at 1400℃ in a baking furnace under air atmosphere for 3h, and tested for hot flexural strength at 1400℃×0.5h. The performance test results are shown in Table 1.

[0104] Table 1 Performance test data

[0105]

[0106] As can be seen from Table 1, the refractory castables for the main ditch of blast furnace iron-making prepared in Comparative Examples 1-3, although their bulk density, flexural strength and compressive strength can basically meet the use at a low temperature of 110°C, when the temperature rises to 1400°C, their flexural strength and compressive strength are significantly low. The refractory castables for the main ditch of blast furnace iron-making prepared in the embodiment of the present invention have significantly better performance in the high temperature stage than the comparative example, with a flexural strength of more than 12.5Mpa and a compressive strength of more than 64Mpa in the cold state after burning at 1400°C×3h, a linear change rate of less than +0.3%, and a flexural strength of more than 4.4Mpa in the hot state at 1400°C×0.5h. In summary, the refractory castables for the main ditch of blast furnace iron-making prepared in the present invention have excellent heat resistance, high strength and hardness, so that they have good corrosion resistance, thermal shock resistance and oxidation resistance, and can extend their service life.

[0107] The above description is only a preferred embodiment of the present invention and does not limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A refractory castable for a blast furnace main ditch, characterized in that: The invention comprises the following raw materials in parts by weight: The modified graphite is obtained by subjecting graphite oxide to an interfacial chemical deposition reaction in a mixed aqueous solution of Mg salt and Al salt to form Mg(OH)2 / Al(OH)3 coated graphite particles, then calcining in an inert atmosphere to form MgO / Al2O3 coated graphite particles, and then surface modification with terminal carboxyl polyethylene glycol silane; the antioxidant is a compound of magnesium carbide, boron carbide and silicon powder.

2. The refractory castable for the main ditch of blast furnace iron tapping according to claim 1, characterized in that: The mass ratio of the graphite oxide, Mg salt and Al salt is 10:(1.5-2.5):(3.5-6.5); the mass ratio of the MgO / Al2O3 coated graphite particles and the terminal carboxyl polyethylene glycol silane is 10:(0.6-1).

3. The refractory castable for the main ditch of blast furnace iron tapping according to claim 1, characterized in that: The structural formula of the carboxyl-terminated polyethylene glycol silane is: Wherein R is -CH3 or -CH2CH3, and the number average molecular weight of the polyethanol chain segment is 400-800.

4. The refractory castable for the main ditch of blast furnace iron tapping according to claim 1, characterized in that: In the antioxidant, the mass ratio of magnesium carbide, boron carbide and silicon powder is 1:(1-2):(1-2).

5. The refractory castable for the main ditch of blast furnace iron tapping according to claim 1, characterized in that: The modified graphite is obtained by a preparation method comprising the following steps: (P1) thermally oxidizing graphite to obtain graphite oxide; (P2) dissolving a nonionic surfactant in a mixed aqueous solution of Mg salt and Al salt, and then dispersing graphite oxide therein to obtain a suspension; then dropping an alkali solution into the suspension, and performing an interfacial chemical deposition reaction under stirring, and after the reaction is completed, washing, filtering, and drying to obtain Mg(OH)2 / Al(OH)3 coated graphite particles; (P3) calcining the Mg(OH)2 / Al(OH)3 coated graphite particles under an inert atmosphere to obtain MgO / Al2O3 coated graphite particles; (P4) MgO / Al2O3 coated graphite particles and carboxyl-terminated polyethylene glycol silane are added to a non-polar organic solvent, and the modified graphite is obtained after stirring and reacting.

6. The refractory castable for the main ditch of blast furnace iron tapping according to claim 5, characterized in that: In step (P1), the graphite is at least one of artificial graphite, natural graphite, and graphitized mesophase carbon microspheres, and its particle size D50 is 10 to 15 μm; the thermal oxidation conditions are: 250 to 350° C. for 1 to 3 hours; and / or In step (P2), the nonionic surfactant is a polyoxyethylene fatty acid ester, and its usage is 1-3wt% of the mixed aqueous solution; the Mg salt is at least one of MgCl2, MgSO4, and Mg(NO3)2, and the Al salt is at least one of AlCl3, Al2(SO4)3, and Al(NO3)3; the concentration of the Mg salt in the mixed aqueous solution is 0.5-1.5wt%, and the concentration of the Al salt is 1.5-3.5wt%; the alkali solution is an aqueous solution of NaOH or KOH, and its concentration is 5-10wt%, and its usage is 0.4-0.8 times the mass of the mixed aqueous solution; and / or In step (P2), the stirring speed is 60 to 120 rpm; the conditions of the interfacial chemical deposition reaction are: the temperature is 40 to 60°C, the alkali solution is added within 30 to 60 minutes and the stirring is continued for 20 to 40 minutes after the addition is completed; the washing is performed with pure water, and the filtration is performed until the pH value of the filtrate is 6.8 to 7.2; the drying conditions are: the temperature is 80 to 100°C and the time is 8 to 12 hours.

7. The refractory castable for the main ditch of blast furnace iron tapping according to claim 5, characterized in that: In step (P3), the inert atmosphere is nitrogen and / or argon, and the calcination conditions are: keeping warm at 400-500° C. for 1-3 hours; and / or In step (P4), the ratio of the MgO / Al2O3 coated graphite particles to the non-polar organic solvent is 10g: (80-150)mL; the non-polar organic solvent is at least one of toluene and xylene; the stirring reaction conditions are: heating to 50-60°C at a rotation speed of 150-300rpm and reflux reaction for 3-6h.

8. The refractory castable for the main ditch of blast furnace iron tapping according to claim 1, characterized in that: The particle size of the dense corundum is 3 to 8 mm; the particle size of the white corundum is 1 to 3 mm; the particle size of the silicon carbide is 0.5 to 1 mm; the particle size D50 of the α-Al2O3 micropowder is 3 to 10 μm; the particle size D50 of the ρ-Al2O3 micropowder is 3 to 10 μm; the particle size of the antioxidant is 200 to 400 mesh; and / or In the dense corundum and white corundum, Al2O3≥99wt%, Fe2O3≤0.1wt%, SiO2≤0.1wt%; in the silicon carbide, SiC≥97wt%, SiO2≤0.4wt%, Fe2O3≤0.3wt%; in the α-Al2O3 micropowder, Al2O3≥99.0wt%; in the ρ-Al2O3 micropowder, Al2O3≥98.0wt%; and / or The organic fiber is at least one of nylon fiber, polyethylene fiber and polypropylene fiber, with a diameter of 4 to 8 μm and a length of 8 to 15 mm; the water reducer is a polycarboxylic acid water reducer with a water reduction rate of 18 to 22%.

9. The method for preparing the refractory castable for the main ditch of blast furnace iron tapping according to any one of claims 1 to 8, characterized in that: The following steps are involved: (S1) adding α-Al2O3 micropowder, ρ-Al2O3 micropowder, modified graphite and antioxidant into a container and mixing and stirring to obtain a mixed fine material; (S2) adding dense corundum, white corundum and silicon carbide into another container and mixing and stirring to obtain mixed granules; (S3) adding the mixed fine material obtained in (S1) to the mixed granular material obtained in (S2), and then adding organic fiber and a water reducing agent for mixing and stirring, thereby obtaining a refractory castable for a blast furnace main ditch.

10. The water-adding pouring construction method for refractory castables for the main trough of blast furnace iron production as claimed in any one of claims 1 to 8, characterized in that: The amount of water added is 3-5wt% of the refractory castable.

Citation Information

Patent Citations

  • Antioxidant blast furnace iron runner castable and preparation method thereof

    CN117247272A

Cited By

  • VD furnace cover castable lining and preparation method thereof

    CN120398554A

  • A VD furnace cover castable lining and preparation method thereof

    CN120398554B